Essence of intellect and logic in the farabian tradition (Journal of Philosophy Culture and Political Science, 2015)
The article gives an analysis of that during the Islamic Middle Ages the Al-Farabi's doctrine on intellect and logic took pride of place. The main point in this part of his philosophy is a belief in the power of human mind, as well as the human ability to discover the diversity of the world around owing to logic. Al-Farabi places no boundaries to human mind and his ability to penetrate into the essence of things. Value relevance of the Al- Farabi's philosophical views is that it considers human reason, as coming from the Single Essence, as making human in form of consubstantial entities in God. Therefore, Al-Farabi fundamentally studied intellect. Intellect is a strict universality; following it means to be reasonable. Intellect acts as a universal principle of the formation of human personality and the cognitive process as a whole.
Keywords: intellect; logic; being; perfection; prudence; four intel¬lects; apodeictics; dialectics.